The Effect of Problem Based Learning on Cognitive Outcome in Science Subject in Junior High School : Topic Water Pollution - Rini, Endah Setia (IJIS Edu : Indonesian Journal of Integrated Science Education, 2020)
The research aimed to determine the effect off Problem Based Learning in science learning on cognitive outcomes of 7th grade at junior high school on the topic of water pollution. This research is an experimental research. The research sample was selected by random sampling technique. The research data was collected through pre-test and post-test using cognitive learning outcome instruments. Analysis data using t-test. The results showed the Problem Based Leearning significantly improved on cognitive outcome this can be seen from the increase in the post-test in the experimental group compared to the control group (74.43>68.23). Based on the resultd of these studies indicate that the use of Problem Based Learning affectes the learning of science on the cognitive outcomes of 7th grade at junior high school on the topic of water pollution.